THU0049 29-KDA fibronectin fragment suppressed HMGB1-dependent autophagy pathway in human articular chondrocytes. (15th June 2017) - Choi, M; Park, IY; Son, KM; Hwang, HS; Kim, HA
Abstract : Background: Fibronectin fragments found in synovial fluid induce the catabolic responses in cartilage. High mobility group protein Box 1 (HMGB1), a damage-associated molecular pattern (DAMP), resides in the nucleus, translocates into the cytosol in response to various stimuli, and is subsequently released into the extracellular space. Objectives: In this study, we investigated the effect of 29-kDa fibronectin fragment (29-kDa FN-f) on HMGB1-mediated autophagy pathway in primary human chondrocytes. Methods: Human articular chondrocytes were enzymatically isolated from articular cartilage. The mRNA and protein levels of HMGB1 were measured by quantitative real-time PCR (qRT PCR) and Western blot analysis. The translocation of nuclear HMGB1 into cytoplasm was determined by western blot and immunofluorescence microscopy. Activation of mammalian target of rapamycin (mTOR), protein kinase B (Akt) and 1A/1B-light chain 3 (LC3) was measured by western blot analysis. Interaction of HMGB1 and Beclin-1 were evaluated by immunoprecipitation (IP). Release of HMGB1 into extracellular medium was measured by ELISA. Results: HMGB1 was significantly reduced in human osteoarthritis (OA) cartilage compared to normal cartilage. qRT PCR and Immunoblotting assay revealed that 29-kDa FN-f significantly reduced expression of HMGB1 at the mRNA and protein levels and also led to the translocation of the nuclear HMGB1 into the cytoplasm, together with decreased levels of Beclin-1 and phosphorylated Bcl-2. Using IP analysis, we demonstrated that in the presence of 29-kDa FN-f the association of HMGB1 and Beclin-1, which led to HMGB1-dependent autophagy pathway, was decreased, whereas the association of Bcl-2 and Beclin-1 was increased. In addition, prolonged treatment with 29-kDa FN-f significantly increased the release of HMGB1 into the culture medium. A variety of evidence, including down-regulated LC3-II, an autophagy marker, and increased phosphorylated 4EBP1 and p70S6K, substrates of mTOR, revealed that 29-kDa FN-f subsequently suppressed autophagy in primary chondrocytes by activating Akt/mTOR signaling pathway. Conclusions: These results demonstrated that 29-kDa FN-f has a harmful impact on chondrocytes through suppressing HMGB1-dependent autophagy pathway and releasing HMGB1, DAMP, to extracellular space. References: Kwak et al. Current Understanding of HMGB1-mediated Autophagy. J. Bacteriol. Virol. 43 (2013) 148–154. Heinola et al. High mobility group box-1 (HMGB-1) in osteoarthritic cartilage. Clinical. Exp. Rheumatol. 28 (2010) 511–518. Hwang et al. Fibronectin fragment-induced expression of matrix metalloproteinases is mediated by MyD88-dependent TLR-2 signaling pathway in human chondrocytes. Arthritis. Res. Therapy. 17 (2015) 320. Acknowledgements: This study was supported by a grant (HI14C2248 and HI15C2699) from the Korean Health Technology R&D Project, Ministry of Health & Welfare, Republic of Korea and the Basic Science Research Program through the National Research Foundation (NRF) of Korea funded by the Ministry of Education (2014R1A1A2059823). Disclosure of Interest: None declared